2018
DOI: 10.2147/ndt.s181948
|View full text |Cite
|
Sign up to set email alerts
|

Low levels of serum magnesium are associated with poststroke cognitive impairment in ischemic stroke patients

Abstract: PurposePopulation-based studies have revealed a high prevalence of cognitive impairment after stroke. We aimed to determine the impact of serum magnesium (Mg2+) levels on the occurrence of poststroke cognitive impairment (PSCI).Patients and methodsAcute ischemic stroke patients (n = 327) were enrolled in our study and serum Mg2+ levels were assessed on admission. The cognitive performance of each patient was evaluated using the Mini–Mental State Examination (MMSE) at a 1-month follow-up visit.ResultsOne hundre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 38 publications
2
8
1
Order By: Relevance
“…The findings of our study were consistent with the results of most of the previous studies in both humans and animals [7][8][9][10][11][12][13][14][15][16][23][24][25][26]. A cross-sectional study conducted in…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The findings of our study were consistent with the results of most of the previous studies in both humans and animals [7][8][9][10][11][12][13][14][15][16][23][24][25][26]. A cross-sectional study conducted in…”
Section: Discussionsupporting
confidence: 93%
“…The findings of our study were consistent with the results of most of the previous studies in both humans and animals [7][8][9][10][11][12][13][14][15][16][23][24][25][26]. A cross-sectional study conducted in Spain on 447 participants found that increased intake of Mediterranean-diet components including walnuts is linked to better cognitive function and increased working memory in elderly at high cardiovascular risk [27].…”
Section: Discussionsupporting
confidence: 92%
“…In a case-control study of 30 patients (15 with Alzheimer's disease and 15 with mild cognitive impairment) and 15 control participants, lower magnesium concentrations were found among patients with Alzheimer's disease and mild cognitive impairment (Balmus et al, 2017). Evidence from animal studies supports a link between circulating magnesium and cognition (Slutsky et al, 2010;Li et al, 2014;Huang et al, 2018;Tu et al, 2018). Low magnesium impairs cognition (Tu et al, 2018) and FIGURE 2 | Interaction between serum magnesium concentrations, diabetes, and gender with cognition.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from animal studies supports a link between circulating magnesium and cognition (Slutsky et al, 2010;Li et al, 2014;Huang et al, 2018;Tu et al, 2018). Low magnesium impairs cognition (Tu et al, 2018) and FIGURE 2 | Interaction between serum magnesium concentrations, diabetes, and gender with cognition. Values represent the adjusted mean (SD) of MRT derived from multivariable linear regression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation